2015
DOI: 10.1104/pp.114.253799
|View full text |Cite
|
Sign up to set email alerts
|

WRKY42 Modulates Phosphate Homeostasis through Regulating Phosphate Translocation and Acquisition in Arabidopsis  

Abstract: The Arabidopsis (Arabidopsis thaliana) WRKY transcription factor family has more than 70 members, and some of them have been reported to play important roles in plant response to biotic and abiotic stresses. This study shows that WRKY42 regulated phosphate homeostasis in Arabidopsis. The WRKY42-overexpressing lines, similar to the phosphate1 (pho1) mutant, were more sensitive to low-inorganic phosphate (Pi) stress and had lower shoot Pi content compared with wild-type plants. The PHO1 expression was repressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
138
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(138 citation statements)
references
References 43 publications
(96 reference statements)
0
138
0
Order By: Relevance
“…It was shown that WRKY family genes are involved in tolerance to phosphate starvation in rice: overexpression of WRKY74 gene increase tolerance to phosphate starvation, while lines with low WRKY74 level were sensitive to this stress [33]. In Arabidopsis , WRKY42 regulates phosphate homeostasis: WRKY42 overexpressing lines were more sensitive to phosphate deficiency [34]. However, overexpression of WRKY45 in Arabidopsis increased phosphate uptake [35].…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that WRKY family genes are involved in tolerance to phosphate starvation in rice: overexpression of WRKY74 gene increase tolerance to phosphate starvation, while lines with low WRKY74 level were sensitive to this stress [33]. In Arabidopsis , WRKY42 regulates phosphate homeostasis: WRKY42 overexpressing lines were more sensitive to phosphate deficiency [34]. However, overexpression of WRKY45 in Arabidopsis increased phosphate uptake [35].…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence reveals that WRKY genes are also involved in plant responses to nutrient deficiency or toxicity. For example, a number of WRKYs regulate phosphate uptake and translocation in Arabidopsis (Devaiah et al, 2007;Chen et al, 2009;Wang et al, 2014;Su et al, 2015). Interestingly, W-boxes, the DNA binding sites of WRKY proteins, are enriched in the promoters of many Fe deficiency-responsive genes .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, accumulating evidence has demonstrated that WRKY transcription factors also take part in the responses to nutritional stresses. For example, some WRKYs (WRKY6/42/45/75) regulate phosphate starvation responses in Arabidopsis (Devaiah et al, 2007;Chen et al, 2009;Wang et al, 2014;Su et al, 2015). Meanwhile, WRKY6 is involved in the response to boron deficiency (Kasajima et al, 2010).…”
mentioning
confidence: 99%
“…Two conserved motifs were identified into AM-induced PT promoters, one of this is P1BS and the other one is named MYCS (mycorrhiza transcription factor binding sequence) and both are involved in the activation of AM-responsive PT genes (Chen et al, 2010). In Arabidopsis plants, four WRKY proteins have been reported to be involved in Pi starvation signaling pathway (Devaiah et al, 2007;Chen et al, 2009;Wang et al, 2014b;Su et al, 2015). WRKY42, WRKY45 and WRKY75 have been identified as positive regulators of PHT1;1 genes (Devaiah et al, 2007;Su et al, 2015).…”
Section: Phosphate Transport In the Arbuscular Mycorrhizal Symbiosismentioning
confidence: 99%